Terapi Sosial Kognitif terhadap Gaya Hidup Pasien dengan Hipertensi - Bakti, Surya; Triyanto, Endang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify research articles that describe the effectiveness of cognitive and social therapy in increasing lifestyle compliance in hypertensive patients. The research uses a literature review of national and international indexed journals. The research results showed that from 6 articles, it was found that social cognitive therapy was significantly related to the lifestyle of hypertensive patients. The components of social cognitive therapy, namely social factors, personal factors, and environmental factors, must be sustainable to create high lifestyle compliance. In conclusion, the components of social cognitive theory will influence individuals to live a lifestyle modified according to the physical conditions experienced. These three factors must be sustainable to produce high compliance with the lifestyle. Keywords: Lifestyle, Hypertension Patients, Cognitive Social Therapy